COVID-19-related acute necrotizing encephalopathy with brain stem involvement in a patient with aplastic anemia. Issue 5 (September 2020) - Dixon, Luke; Varley, James; Gontsarova, Anastassia; Mallon, Dermot; Tona, Francesca; Muir, David; Luqmani, Asad; Jenkins, Ieuan Harri; Nicholas, Richard; Jones, Brynmor; Everitt, Alex
Abstract : Objective: To describe a novel case of coronavirus disease 2019 (COVID-19)-associated acute necrotizing encephalopathy (ANE) in a patient with aplastic anemia where there was early brain stem-predominant involvement. Methods: Evaluation of cause, clinical symptoms, and treatment response. Results: A 59-year-old woman with a background of transfusion-dependent aplastic anemia presented with seizures and reduced level of consciousness 10 days after the onset of subjective fever, cough, and headache. Nasopharyngeal swab testing for severe acute respiratory syndrome coronavirus (SARS-CoV-2) was positive, and CT during admission demonstrated diffuse swelling of the brain stem. She required intubation and mechanical ventilation for airway protection, given her reduced level of consciousness. The patient's condition deteriorated, and MRI on day 6 demonstrated worsening brain stem swelling with symmetrical hemorrhagic lesions in the brain stem, amygdalae, putamina, and thalamic nuclei. Appearances were consistent with hemorrhagic ANE with early brain stem involvement. The patient showed no response to steroid therapy and died on the eighth day of admission. Conclusions: COVID-19 may be associated with an acute severe encephalopathy and, in this case, was considered most likely to represent an immune-mediated phenomenon. As the pandemic continues, we anticipate that the spectrum of neurologic presentation will broaden. It will be important to delineate the full clinical range of emergent COVID-19-related neurologic disease.